Relationship conflict, appraisals, and disillusionment: The moderating role of depression. (March 2021) - Weigel, Daniel J.; Shrout, M. Rosie
Abstract: Depression is one of the most common mental health disorders and one that can impact multiple aspects of a person's life, including one's close relationships. The present study applied a stress perspective to examine how a person's depressive symptoms help shape how individuals interpret conflict in their relationships and whether that conflict is associated with heightened relationship disillusionment. Using data collected from 476 romantically-involved individuals, analyses revealed that heightened relationship conflict was associated with more negative conflict-related appraisals and blame, which in turn were linked to greater relationship disillusionment. Moderation analyses identified depressive symptoms as an individual vulnerability that heightened the negative effects of conflict. These findings reveal the importance of individuals' perceptions and depressive symptoms on conflict's relational toll.